The Transformation of Husbands' Roles in Indonesian Migrant Worker Families and the Implications for Children's Islamic Education - Umar, A.; Astuti, Nita Yuli; Nasikhin (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study explores how husbands fulfil marital responsibilities in Indonesian migrant worker (PMI) families and examines the implications for children’s Islamic education. Using a qualitative approach with a narrative inquiry design, data were collected through in-depth interviews with five PMI husbands (TS1–TS5), their wives (W1–W5), and one focal child from each household (C1–C5). Data credibility was strengthened through source triangulation across family members, field notes, and member checking. Data analysis followed the Miles and Huberman interactive model. The findings indicate a selective reconfiguration of husbands’ roles: direct financial provision to wives, emotional support, and a sense of protection are generally weak, while husbands remain central as household financial managers who administer remittances and allocate resources to meet children’s needs. Within this role configuration, children’s Islamic education tends to emphasize discipline, independence, responsibility, simplicity, and prudent resource management, alongside awareness of mothers’ sacrifices. However, limited spousal emotional engagement constrains the transmission of affective and relational dimensions of Islamic education, risking an approach that becomes more normative-functional than holistic and spiritually grounded. This study contributes to debates on gender, family responsibility, and religious education in transnational contexts by foregrounding the multi-voiced dynamics within migrant worker families and offering implications for family-based Islamic education that is responsive to social and emotional realities.